Application of the Scale for the Assessment of Feeding Interaction (SVIA) to Children With Autism Spectrum Disorder - Catino, Elena; Perroni, Giorgia; Di Trani, Michela; Alfonsi, Chiara; Chiarotti, Flavia; Cardona, Francesco (Frontiers in Psychiatry, 2019)
Background and objectives: Feeding problems occur more frequently among children with Autism Spectrum Disorder (ASD). The aim of thisstudy was to analyse eating difficulties of ASD children through the direct observation of the caregiver-child co-regulation system. Methods: We compared 60 ASD children with a control group of 50 typically developing Italian children on the Scale for the Assessment of Feeding Interaction (SVIA). The Brief Autism Mealtime Behaviour Inventory (BAMBI) was used to define the presence of an eating disorder. Results: The ASD group showed higher scores on all dimensions of the SVIA compared tothe control group. The SVIA and the BAMBI showed significant correlations. In a second step, the ASD sample was divided into two subgroups, children with and without feeding difficulties. The comparison between the ASD subgroups with the control group on the SVIA scales showed significant differences on all dimensions. Finally, significant differences emerged between the two ASD subgroups in three SVIA dimensions. Conclusion: These data suggest the importance of direct observation of feeding in the assessment of children with ASD. The SVIA seems to be able to point out some feeding difficulties in these subjects and to discriminate ASD with and without an eating disorder. Critical aspects of the application of SVIA to autistic children are discussed.